The Republicans : a history of the Grand Old Party - Gould, Lewis L. (Oxford University Press, 2015)
A new edition of Lewis L. Gould's history of the Republican party. It retains the features that made the first edition a success - a fast-paced account of Republican fortunes, a deep knowledge of the evolution of national political history, and an acute feel for the interplay of personalities and ideology. All the main players in the Republican story are captured in penetrating sketches and deft analysis.